2008
DOI: 10.1090/s0002-9939-08-09622-6
|View full text |Cite
|
Sign up to set email alerts
|

An algebraic independence result for Euler products of finite degree

Abstract: Abstract. We investigate the algebraic independence of some derivatives of certain multiplicative arithmetical functions over the field C of complex numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For a detailed account of recent results on this topic, we refer to [23]. Let us also mention that functional independence of general families of L-functions (including the ones that are associated to cusp forms) was shown by Zaharescu and Zaki [28] using a purely algebraic method. Let us also mention that functional independence of general families of L-functions (including the ones that are associated to cusp forms) was shown by Zaharescu and Zaki [28] using a purely algebraic method.…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed account of recent results on this topic, we refer to [23]. Let us also mention that functional independence of general families of L-functions (including the ones that are associated to cusp forms) was shown by Zaharescu and Zaki [28] using a purely algebraic method. Let us also mention that functional independence of general families of L-functions (including the ones that are associated to cusp forms) was shown by Zaharescu and Zaki [28] using a purely algebraic method.…”
Section: Introductionmentioning
confidence: 99%
“…We should mention that approximation type results in some nonstandard settings have been the subject of important research. [54] with the help of a purely algebraic method. The author [5] showed that weighted averages of Gauss sums can be well approximated by Q-linear combinations of special values of L-functions in which coefficients belonging to the combinations only depend on the parity of the character.…”
Section: Introductionmentioning
confidence: 99%